Quantum-enhanced strategies for surface and phase discrimination - Napoli, Carmine (2021)
The ability to perform high precision measurements underpins a plethora of applications. Several techniques for force sensing, phase estimation and discrimination, as well as surface reconstruction for complex features of three-dimensional samples, have been developed in recent years.